Pengaruh - Permatasari, Ragil Putri; Simbolon, Demsa; Yunita, Yunita (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Precision is an ability to measure the same subject repeatedly with minimum error. Accuracy is an ability to get results that are as close as possible to the results obtained. selecting surveyors who are skilled in a research data collection activity. The level of precision and accuracy of posbindu cadres is still very low in conducting. This research design uses quantitative methods using the Pre-Experimental (One group pre test and post test), where this research is used to see the Precision and Accuracy of Calculations of BMI (Body Mass Index) and RLPP (Waist Hip Circumference Ratio) Adults By Posbindu Cadres . The population is 12 posbindu cadres in the working area of ​​the Nusa Indah Health Center and a sample of 24 cadres. Data analysis used univariate and bivariate data analysis, namely the Wilcoxon Rank test and McNemar test. Research Results There is an influence on the knowledge of cadres getting training interventions for calculating body mass index and waist-hip ratio. It is known that there is an effect of precision and accuracy on calculating body mass index and waist-hip ratio before and after training by cadres at Posbindu in the working area of ​​the Nusa Indah Health Center in Bengkulu City with a P value <0.05 there is a significant effect on BMI precision from before and after posbindu cadre training.